The effects of plant extract with an antibacterial effect (herbromix®') on some antioxidants and blood parameters in heat-stressed broilers - Nurcan DÖNMEZ; Ercan KESKİN (Eurasian Journal of Veterinary Sciences)
ln the study the effects of plant extract (Herbromix®) with an antibacterial effect added to ration on some blood parameters and antioxidants were studied in 80 broiler chicks under heat stress. The chicks were divided into four groups as control (K). plant extract (S), stress (S) and stress + plant extract (SB). The study was carried on 45 days. At first 15 days, herbal extract was administrated to P and SP groups. Second 15 days, heat stress (38 -39 C°) was applied to S and SB groups. Plant extract application was carried on during third 15 days. MDA levels increased significantly (p<0.05) in S and SB groups on the 15th day with heat stress. GSH levels significantly decreased in S group compared with the other groups. At the 15th days with the heat stress application, total protein and cholesterol levels were decreased (p<0.05) and glucose levels increased (p<0.05) in S compared with control group. Except of GSH levels there was no differences between S and SB groups in respect of any parameters. In conclusion, the results determined in the study might be important to demonstrate the negative effects of heat stress on some biochemical and antioxidant parameters: however the plant extract administration has no beneficial effect in heat stress.